2020
DOI: 10.1111/jors.12513
|View full text |Cite
|
Sign up to set email alerts
|

Causal effects of the fracking boom on long‐term resident workers

Abstract: Horizontal drilling innovations revolutionized the U.S. oil and gas industry and facilitated a boom in production in the mid‐2000s in regions with shale and tight‐sands reservoirs. This paper examines the effects of the boom on individual employment and earnings within boom states. We account for endogenous migration decisions by using a novel instrument for oil and gas production in workers' state of residence. We find statistically significant and economically meaningful positive effects of the oil and gas b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The magnitudes are roughly twice as large in Columns 1 and 2 as in Columns 3 and 4, indicating that income increases from oil and gas booms are especially pronounced at the lower end of the income distribution. This is consistent with previous research finding larger income effects for workers who are younger and less educated (Kearney & Wilson, 2018;Winters et al, 2021). Notably, our results in Table 2 confirm that the oil and gas boom income effects found in previous literature are not exclusive to households without children.…”
Section: Oil and Gas Effects On Incomesupporting
confidence: 93%
See 2 more Smart Citations
“…The magnitudes are roughly twice as large in Columns 1 and 2 as in Columns 3 and 4, indicating that income increases from oil and gas booms are especially pronounced at the lower end of the income distribution. This is consistent with previous research finding larger income effects for workers who are younger and less educated (Kearney & Wilson, 2018;Winters et al, 2021). Notably, our results in Table 2 confirm that the oil and gas boom income effects found in previous literature are not exclusive to households without children.…”
Section: Oil and Gas Effects On Incomesupporting
confidence: 93%
“…Child food security for less advantaged groups is expected to be especially responsive to local economic conditions. In particular, food security for children with less educated parents is expected to be especially responsive to oil and gas income in the state because they typically have lower household incomes and the oil and gas boom increased income the most for less educated workers (Kearney & Wilson, 2018; Winters et al, 2021).…”
Section: Empirical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, urbanization brings negative externalities [39][40][41], such as congestion [42], crime, and pollution, which may offset the benefits of using cleaner energy. Third, while gas development positively affects labor market outcomes [43,44], it also raises environmental concerns [45][46][47][48][49][50]. Finally, it remains unclear how government-led urbanization will affect the welfare of rural and urban residents.…”
Section: Conclusion and Policy Remarksmentioning
confidence: 99%
“…This growth is expected to be accelerated by recent Federal legislation, including the Inflation Reduction Act (U.S. EIA, 2023a).2 For example,Feyrer et al (2017) found that new oil and natural gas production from hydraulic fracturing increased local wages and reduced unemployment.Weber (2014) found that expanded natural gas production led to jobs outside of the oil and gas industry. BothAllcott and Kensiton (2018) andWinters et al (2021) found long-term employment gains from oil and gas development Jacobsen et al (2023),. however, found that short-term wage benefits from oil and gas booms can be offset by employment effects when production slows in the long term.…”
mentioning
confidence: 97%